Associations between diet and (in)activity behaviours with overweight and obesity among 10-18-year-old Czech Republic adolescents - de Gouw, Linda; Klepp, Knut-Inge; Vignerová, Jana; Lien, Nanna; Steenhuis, Ingrid H M; Wind, Marianne (Public health nutrition, 2010)
OBJECTIVES: To assess the prevalence of normal weight, overweight and obesity among 10-18-year-old Czech Republic adolescents and to assess the association between energy balance-related behaviours and overweight/obesity. DESIGN: Cross-sectional data from 'The 6th Nation-wide Anthropological Survey of Children and Adolescents 2001 Czech Republic' have been used. SETTING: Height and weight were objectively measured. Data on adolescents' behaviours were assessed with self-reported questionnaires. Background variables were assessed by means of a parental questionnaire. Multi-level logistic regression analyses were conducted to assess behavioural risk factors of being overweight/obese. SUBJECTS: Data on 31,228 adolescents aged 10-18 years were included in the present study. RESULTS: The highest prevalence of being overweight or obese was found among boys and younger adolescents. Boys were more physically active, watched more television (TV) and used the computer more often than did girls. Being on a diet and skipping meals were positively associated with being overweight/obese, independent of gender. In boys (10-14 years old), inverse associations with being overweight/obese were found when being more physically active. Monitoring weight showed inverse relations with being overweight/obese in 15-18-year-old girls. Watching TV more than 7 h a week was positively associated with being overweight/obese in 15-18-year-old girls, and was found to be negatively associated in boys of the same age group. CONCLUSIONS: These behaviours should be targeted when preventing overweight and obesity among Czech Republic adolescents. Studies using better measures of energy balance-related behaviours are needed.
Keywords: logistické modely; Sedentary Behavior; Female; Overweight; dítě; Television; Age Factors; ženské pohlaví; sedavý životní styl; průřezové studie; Logistic Models; Adolescent Behavior; Diet, Reducing; Adolescent; Obesity; pohybová aktivita; stravovací zvyklosti; věkové faktory; lidé; cvičení; Computers; dieta; Humans; Sex Factors; Cross-Sectional Studies; obezita; Diet; Feeding Behavior; Male; sexuální faktory; televize; Czech Republic; mladiství; redukční dieta; index tělesné hmotnosti; nadváha; Česká republika; Motor Activity; Child; počítače; mužské pohlaví; Body Mass Index; Exercise; chování mladistvých; chování dětí; Child Behavior